Limited effectiveness with a 10‐day bismuth‐containing quadruple therapy (Pylera®) in third‐line recue treatment for Helicobacter pylori infection. A real‐life multicenter study. Issue 5 (3rd August 2017) - Rodríguez de Santiago, Enrique; Martín de Argila de Prados, Carlos; Marcos Prieto, Hector Miguel; Jorge Turrión, Miguel Ãngel; Barreiro Alonso, Eva; Flores de Miguel, Alvaro; de la Coba Ortiz, Cristobal; Rodríguez Escaja, Carlos; Pérez Álvarez, Gustavo; Ferre Aracil, Carlos; Aguilera Castro, Lara; García García de Paredes, Ana; et al.
Abstract: Background: Helicobacter pylori antibiotic resistance is an increasing problem worldwide. Pylera ® may be an option as salvage therapy. Aim: To assess the effectiveness, safety, and tolerance of Pylera ® as a third‐line in clinical practice. Materials and Methods: This was a multicenter, observational, prospective database study in four Spanish hospitals. Consecutive H. pylori ‐infected individuals treated with Pylera ® and a proton‐pump inhibitor (PPI) were invited to participate if they had failed to respond to PPI‐clarithromycin‐amoxicillin as first‐line and to levofloxacin‐amoxicillin‐PPI as second‐line therapy. Eradication was tested 4‐8 weeks after Pylera ® using a C 13 ‐urea breath test. Treatment‐related adverse effects (TRAEs) were assessed through a questionnaire and by reviewing databases. A questionnaire on patient satisfaction was completed in the last visit. Results: Of 103 subjects fulfilling the selection criteria, 101 were included in the intention‐to‐treat (ITT) analysis and 97 in the per‐protocol (PP) analysis. A 10 day course was prescribed in all patients. Esomeprazole 40 mg b.i.d. was the most used PPI regimen (ITT=94.1%). Ninety‐seven individuals (ITT=96.04%) completed more than 90% of the treatment. Overall eradication rates were ITT=80.2% (95% confidence interval [CI]: 72.3%‐88.1%) and PP=84.4% (95% CI: 76.8%‐91.8%). One or more TRAEs were experienced by 67.3% (95% CI: 57.7%‐75.7%), all mild or moderate. TRAEs and the number of pills were the main complaints. Conclusion: In an area of high antibiotic resistance to H. pylori, 10‐day Pylera ® plus double‐dose PPI emerged as an alternative as third‐line therapy, although not achieving optimal eradication rates. TRAEs were common but were neither severe nor did they condition compliance.